2021
DOI: 10.1007/s13762-021-03449-1
|View full text |Cite
|
Sign up to set email alerts
|

Field engineering application of agricultural farmland surface runoff pollution treatment by combined bioreactor and constructed wetlands

Abstract: Agricultural non-point pollution is the biggest pollution source in China from 2009, the treatment of agricultural surface runoff is very important to mitigate the eutrophication of rivers and lakes because agricultural surface runoff is one key type of non-point source pollution. In this study, agricultural farmland surface runoff in Chengdu Plain was treated for one year (2017 ~ 2018) by the combination treatment technology of new material (waste fir and Hemlock sawdust as substrate) bioreactor for denitrifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…However, ecological ditches do not perform well at low temperatures, and they may even become N sources (Wang et al, 2017). Luo et al reported that the average removal rate of total nitrogen (TN) from agricultural surface runoff on farmland in constructed wetlands was 29.64% (Luo et al, 2022). Additionally, during heavy rainfall events, this method does not have a good effect to the elevated N concentrations (Wei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, ecological ditches do not perform well at low temperatures, and they may even become N sources (Wang et al, 2017). Luo et al reported that the average removal rate of total nitrogen (TN) from agricultural surface runoff on farmland in constructed wetlands was 29.64% (Luo et al, 2022). Additionally, during heavy rainfall events, this method does not have a good effect to the elevated N concentrations (Wei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%